2014
DOI: 10.3389/fpls.2014.00208
|View full text |Cite
|
Sign up to set email alerts
|

A simple method suitable to study de novo root organogenesis

Abstract: De novo root organogenesis is the process in which adventitious roots regenerate from detached or wounded plant tissues or organs. In tissue culture, appropriate types and concentrations of plant hormones in the medium are critical for inducing adventitious roots. However, in natural conditions, regeneration from detached organs is likely to rely on endogenous hormones. To investigate the actions of endogenous hormones and the molecular mechanisms guiding de novo root organogenesis, we developed a simple metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(138 citation statements)
references
References 22 publications
7
125
0
3
Order By: Relevance
“…We found that excised whole leaves of Arabidopsis can root without hormone supplementation, similarly to leaf blades as previously described (Chen et al, 2014) and at similar percentages (Supplemental Fig. S1, A and B).…”
Section: Vasculature-associated Cell Proliferation Is Required For Desupporting
confidence: 56%
See 4 more Smart Citations
“…We found that excised whole leaves of Arabidopsis can root without hormone supplementation, similarly to leaf blades as previously described (Chen et al, 2014) and at similar percentages (Supplemental Fig. S1, A and B).…”
Section: Vasculature-associated Cell Proliferation Is Required For Desupporting
confidence: 56%
“…Moreover, callus formation, which is a prerequisite for hormonal-induced regeneration, does not appear to occur during endogenous organogenesis, although both processes share regulation (Sugimoto et al, 2010;Liu et al, 2014;Perianez-Rodriguez et al, 2014;Ramirez-Parra et al, 2017). Using a simple method to study de novo root organogenesis without hormone supplementation (Chen et al, 2014;Liu et al, 2014) but applied to whole leaves (Fig. 8A), we found that formation of an endogenous callus is a required step for de novo root organogenesis, and thus we established a direct connection between both regenerative processes.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations